A legal analysis on online pornographic law in Malaysia / Amirul Haziq Ahmad … [et al.] - Ahmad, Amirul Haziq; Wan Azmi, Aisyah Radhiah; Roslan, Nur Fatihah; Abu Hassan, Siti Suraya (2014)
This project paper is about proposal of amendment of regulation of Malaysian law in governing online pornography. The related Acts are Multimedia and Communications Act 1998 and Film Censorship Act 2002. It has been stated by these two Acts that they do not permit censorship on the Internet. The regulations in Malaysia have been conducted by Malaysian Communication and Multimedia Commission (MCMC) in accordance with the Content Code. The MCMC however, proves that Malaysia takes action mainly based on complaints made by internet users. This is one of the loopholes we have found in the execution of the regulation that need to be reformed to maintain the almost flawless law. We have also looked into the regulations in other countries which are United States of America, United Kingdom, Australia and China where the regulations have been observed and critically analysed and compared with the enforcement in Malaysia. Based on the analysis, we adopt the idea of having a specific law for internet pornography, as has been done in China. We also adopt the International Association of Internet Hotlines (INHOPE) recommendation to follow other countries' regulations to legally deal with the issue. We are of the opinion that the term 'audio visual' or 'film' should be included in the Section 292(a) of the Penal Code to penalise offenders related to the online pornography crimes. We also suggest that internet users must self-regulate the websites accessed in order to control the dissemination of the materials that will help to create a better society.